2005
DOI: 10.1212/01.wnl.0000158681.29117.8b
|View full text |Cite
|
Sign up to set email alerts
|

Neuropathy resembling CIDP in patients receiving tumor necrosis factor-α blockers

Abstract: Tumor necrosis factor-alpha (TauNuFalpha) blockers are effective in the treatment of inflammatory arthritis but can induce autoimmune disorders including multiple sclerosis. Described are two patients who developed chronic inflammatory demyelinating polyneuropathy after initiation of anti-TNFalpha treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(65 citation statements)
references
References 11 publications
1
60
0
4
Order By: Relevance
“…Anti-TNF-α agents increase risk rates of malignancies in patients with inflammatory bowel disease [250]. It has been mentioned that two patients with rheumatoid arthritis treated with an anti-TNF-α strategy developed neurological symptoms, including demyelination lesions [251]. Furthermore, it was shown that newborns presented severe neutropenia after their mothers were treated with infliximab for ulcerative colitis during pregnancy [252].…”
Section: Targeting Tnf-α As Treatment For Neurodegenerative Disordersmentioning
confidence: 99%
“…Anti-TNF-α agents increase risk rates of malignancies in patients with inflammatory bowel disease [250]. It has been mentioned that two patients with rheumatoid arthritis treated with an anti-TNF-α strategy developed neurological symptoms, including demyelination lesions [251]. Furthermore, it was shown that newborns presented severe neutropenia after their mothers were treated with infliximab for ulcerative colitis during pregnancy [252].…”
Section: Targeting Tnf-α As Treatment For Neurodegenerative Disordersmentioning
confidence: 99%
“…Previous series emphasized the development of acute or chronic demyelinating neuropathy usually occurring a few months after the onset of TNF-␣ treatment, very often associated with conduction blocks on nerve conduction studies. The prognosis is usually good, without relapse, sometimes only after usual treatments for demyelinating neuropathies 4,5,[7][8][9][10]12 ( Figure 1).…”
Section: Casementioning
confidence: 99%
“…Central nervous system autoimmune demyelinating disorders include anterior and posterior optic neuritis and worsening of multiple sclerosis 4 . Peripheral nervous disorders include Guillain-Barré and Miller-Fischer syndromes, chronic inflammatory demyelinating polyradiculoneuropathy, mononeuritis simplex and multiplex, axonal sensory-motor polineuropathy and even motor neuropathy with multiple conduction blocks [4][5][6][7][8] . Two explanations about these anti-TNF-alpha collateral effects are discussed in the literature 4 : a direct toxic drug aggression or a specific autoantibody production and T cell immune system derangement induced by this group of agents.…”
Section: Motor Neuropathymentioning
confidence: 99%
“…According to proposed criteria 11 , an illness, like neuropathy, can be considered as drug-induced or environmentally associated based on: [1] temporal closed association; [2] lack of likely alternative explanations; [3] stabilization or improvement by interrupting exposure to the presumed inciting agent; [4] rechallenge; [5] biological plausibility; [6] analogy; [7] dose responsiveness; [8] specificity. To report findings of a possible causal relationship between exposure and clinical syndrome, at least 4 of the 8 attribution elements should be present.…”
Section: Motor Neuropathymentioning
confidence: 99%
See 1 more Smart Citation